The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1136/heartasia-2013-010484
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of proinflammatory cytokines in chronic heart failure

Abstract: Background Previous studies suggested that inflammation was involved in chronic heart failure (CHF), but their sample sizes were small. Objective To summarise the clinical cytokine data systematically and emphasise the importance of proinflammatory cytokines in the pathogenesis of CHF, we conducted a meta-analysis of relevant literatures. Methods Articles about cytokines and CHF were searched in Pubmed, EMBASE, Cochrane Library, Chinese National Knowledge Infrastructure and Chinese Wanfang Database. The pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…In contrast, TNF-α deficiency was associated with attenuation of cardiac inflammation and amelioration of adverse left ventricular remodeling and dysfunction in mice subjected to transverse aortic constriction ( Sun et al, 2007 ). Consistent with findings from animal studies implicating TNF-α in the pathogenesis of heart failure, circulating levels of TNF-α have consistently been shown to be elevated in patients with chronic heart failure ( Liu et al, 2014 ).…”
Section: Inflammatory Mediators: Chemokines and Cytokinessupporting
confidence: 53%
See 1 more Smart Citation
“…In contrast, TNF-α deficiency was associated with attenuation of cardiac inflammation and amelioration of adverse left ventricular remodeling and dysfunction in mice subjected to transverse aortic constriction ( Sun et al, 2007 ). Consistent with findings from animal studies implicating TNF-α in the pathogenesis of heart failure, circulating levels of TNF-α have consistently been shown to be elevated in patients with chronic heart failure ( Liu et al, 2014 ).…”
Section: Inflammatory Mediators: Chemokines and Cytokinessupporting
confidence: 53%
“…In contrast, genetic deletion of IL-6 ameliorated pressure overload-induced adverse left ventricular remodeling and dysfunction in mice ( Zhao et al, 2016 ). In patients with chronic heart failure, elevated circulating levels of IL-6 have been reported ( Liu et al, 2014 ).…”
Section: Inflammatory Mediators: Chemokines and Cytokinesmentioning
confidence: 99%
“…Previous studies identified elevated proinflammatory cytokines in the brain in mice with chronic heart failure which was associated with increased microglial activation and impaired cognitive performance [26]. Patients in chronic heart failure also exhibit higher levels of proinflammatory cytokines including TNF-α, IL-6, IL-1β, and C-reactive protein [33]. Inflammatory cytokines are known to cross the blood-brain barrier [34].…”
Section: Discussionmentioning
confidence: 99%
“…The release of these pro-inflammatory cytokines promotes atherogenesis by enhancing the release of adhesion molecules, resulting in early monocyte and lymphocyte recruitment in the intima (8). Furthermore, these pro-inflammatory cytokines are considered decisive factors in the pathogenesis and mortality of heart failure (9).…”
Section: Introductionmentioning
confidence: 99%